(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
Artificial Intelligence (AI) has emerged as a transformative force in various sectors, and education is no exception. From personalized learning to intelligent tutoring systems and predictive analytics, AI offers the potential to revolutionize how students learn and how educators teach. This paper explores the various applications of AI in education, the opportunities it presents, and the ethical and practical challenges associated with its integration into educational settings. We analyze how AI is being implemented in personalized learning platforms, administrative functions, assessment tools, and student success prediction. The paper also discusses issues such as data privacy, algorithmic bias, and the future of AI-powered education. Keywords: Artificial Intelligence, Education, Personalized Learning, Predictive Analytics, Ethical Challenges, Learning Technologies, Intelligent Tutoring Systems.